Central Exclusive Higgs Boson Production in the ATLAS Experiment at the LHC - Juránek, Vojtěch; Juránek Vojtěch (České vysoké učení technické v Praze, 2011)
Central Exclusive Higgs Boson Production in the Atlas Experiment

Central Exclusive Higgs Boson Production in the Atlas Experiment
Central Exclusive Higgs Boson Production in the ATLAS Experiment at the LHC
Keywords: Higgs boson, diffraction, ATLAS, central exclusive production